Analysing mine emergency management needs: a cognitive work analysis approach. (2015) - Xiao, Tania; Horberry, Tim; Cliff, David
In this paper, we argue that cognitive work analysis (CWA), a framework for analysing, modelling and designing complex work systems, is an effective approach to determine the emergency management needs of mine operators. To demonstrate, we applied work domain analysis (WDA), the first phase of the CWA framework, to the analysis of the mine emergency management needs of control room operators in an Australian underground coal mine context. Overall, we found that CWA supported a holistic approach to the analysis of emergency management needs by capturing requirements that involved (a) emergency and routine operations, and (b) social and technical aspects of the work. We conclude with implications for the development of procedures, technology and training in underground coal mine emergency management systems.